Forage Testing - Joao M. Vendramini; Maria L. Silveira; John D. Arthington; Ann R. Blount (EDIS, 2009)
Revised! SS-AGR-63, a 4-page fact sheet by J. M. Vendramini, M. S. Silveira, J. D. Arthington, and A. R. Blount, provides basic information about forage testing procedures at the UF/IFAS Forage Extension Testing Laboratory, where to send samples, how to interpret the testing results, and how to collect a sample. Includes references. Published by the UF Department of Agronomy, February 2009.